Low-cost glass ionomer cement as ART sealant in permanent molars: a randomized clinical trial - Daniela HESSE; Clarissa Calil BONIFÁCIO; Camila de Almeida Brandão GUGLIELMI; Carolina da FRANCA; Fausto Medeiros MENDES; Daniela Prócida RAGGIO (Sociedade Brasileira de Pesquisa Odontológica, 2015)
Clinical trials are normally performed with well-known brands of glass ionomer cement (GIC), but the cost of these materials is high for public healthcare in less-affluent communities. Given the need to research cheaper materials, it seems pertinent to investigate the retention rate of a low-cost GIC applied as atraumatic restorative treatment (ART) sealants in two centers in Brazil. Four hundred and thirty-seven 6-to-8-year-old schoolchildren were selected in two cities in Brazil. The children were randomly divided into two groups, according to the tested GIC applied in the first permanent molars. The retention rate was evaluated after 3, 6 and 12 months. Kaplan-Meier survival analysis and the log-rank test were performed. The variables were tested for association with sealant longevity, using logistic regression analyses (α = 5%). The retention rate of sealants after 12 months was 19.1%. The high-cost GIC brand presented a 2-fold-more-likely-to-survive rate than the low-cost brand (p < 0.001). Significant difference was also found between the cities where the treatments were performed, in that Barueri presented a higher sealant survival rate than Recife (p < 0.001). The retention rate of a low-cost GIC sealant brand was markedly lower than that of a well-known GIC sealant brand.